Food studies in Latin American literature : perspectives on the gastronarrative - Aguila, Rocío del, 1975-; Miseres, Vanesa (Food and foodways (Fayetteville, Ark.), 2021)
"Collection of essays analyzing a wide array of Latin American narratives through the lens of food studies"--